Access to primary care and computed tomography use in the emergency department - M. Fernanda Bellolio; Shawna D. Bellew; Lindsey R. Sangaralingham; Ronna L. Campbell; Daniel Cabrera; Molly M. Jeffery; Nilay D. Shah; Erik P. Hess (BMC, 2018)
Abstract Background The decision to obtain a computed tomography CT scan in the emergency department (ED) is complex, including a consideration of the risk posed by the test itself weighed against the importance of obtaining the result. In patients with limited access to primary care follow up the consequences of not making a diagnosis may be greater than for patients with ready access to primary care, impacting diagnostic reasoning. We set out to determine if there is an association between CT utilization in the ED and patient access to primary care. Methods We performed a cross-sectional study of all ED visits in which a CT scan was obtained between 2003 and 2012 at an academic, tertiary-care center. Data were abstracted from the electronic medical record and administrative databases and included type of CT obtained, demographics, comorbidities, and access to a local primary care provider (PCP). CT utilization rates were determined per 1000 patients. Results A total of 595,895 ED visits, including 98,001 visits in which a CT was obtained (16.4%) were included. Patients with an assigned PCP accounted for 55% of all visits. Overall, CT use per 1000 ED visits increased from 142.0 in 2003 to 169.2 in 2012 (p < 0.001), while the number of annual ED visits remained stable. CT use per 1000 ED visits increased from 169.4 to 205.8 over the 10-year period for patients without a PCP and from 118.9 to 142.0 for patients with a PCP. Patients without a PCP were more likely to have a CT performed compared to those with a PCP (OR 1.57, 95%CI 1.54 to 1.58; p < 0.001). After adjusting for age, gender, year of visit and number of comorbidities, patients without a PCP were more likely to have a CT performed (OR 1.20, 95% CI 1.18 to 1.21, p < 0.001). Conclusions The overall rate of CT utilization in the ED increased over the past 10 years. CT utilization was significantly higher among patients without a PCP. Increased availability of primary care, particularly for follow-up from the ED, could reduce CT utilization and therefore decrease costs, ED lengths of stay, and radiation exposure.